STUDENTS' PROBLEMS IN SPEAKING FOR SOCIAL PURPOSES CLASS - Angela Nirmala Nariswari; Listyani Listyani (Universitas Kristen Satya Wacana, 2021)
This study presents a quantitative study conducted in a private university in Central Java, Indonesia. The main aim of this study is to find problems and solutions in Speaking for Social Purposes class. A survey was done on seventy-four (74) students from an English Department (ED) about the difficulties and solutions they experienced in the speaking class. Hopefully, this study will be beneficial for both teachers and students of speaking classes.